Prevalence of Depression in Vitiligo Patients-A Systematic Review and Meta-Analysis - Vinita John; Mohammed Omar Alsadi (Medsci Publications, 2022)
Background: the incidence of depression in vitiligo patients ranges from 10% to over 60%, depending on the outcome measures, sample size and study population. The purpose is to estimate the prevalence of depression among vitiligo patients by conducting a systematic review and metanalysis of published studies. Methods: we conducted a literature search on Medline via PubMed, Scopus, web of science and Cochrane library. Results: 35 studies finally met our inclusion criteria. Our findings showed that the overall prevalence of depression among patients with vitiligo was 35 % (26%-45). Moreover, we observed a variation in the prevalence based on the used tool. For example, the GHQ revealed 30% (20%-39%) and the HDRS revealed 50% (44% - 57%). Our analysis demonstrated no significant differences between vitiligo and healthy cases in terms of HDRS and DBI. Moreover, there was no significant differences between vitiligo and psoriasis in terms of GHQ and BDI scores. Conclusion: in conclusion the current evidence suggests that patients with vitiligo have a high risk and prevalence of depression, different questionnaires have yielded variable prevalence due to the different domains and validation method.